2018
DOI: 10.22225/ga.23.1.658.44-52
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pupuk Kandang Ayam dan Biourine Terhadap Pertumbuhan dan Hasil Dari Benih dan Punggul Tanaman Kangkung Darat (Ipomea Reptans)

Abstract: This study aims to determine the effect of chicken manure and biourine on the growth of stem of ground water kangkung, so it is known that the best type of fertilizer used for growth and yield of kangkung plants after the first harvest. This experiment used a randomized block design (RBD) with a factorial experimental pattern consisting of two factors. The first factor is the dosage of biourine (B) consisting of 4 levels ie B0: control, B1: 200 L ha-1, B2: 400 L ha-1, and B3: 600 L ha-1. The second factor is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Pohan (2021) revealed that Water Spinach is resistant to drought, has strong adaptability to various environmental conditions, and has a short harvest period. The research results by Sudewa and Mudra (2018) reported that manure could increase the growth and yield of water spinach. Water spinach can be planted repeatedly, but subsequent plantings are not as good as the results of the first planting due to the decreased growth of water spinach.…”
Section: Introductionmentioning
confidence: 99%
“…Pohan (2021) revealed that Water Spinach is resistant to drought, has strong adaptability to various environmental conditions, and has a short harvest period. The research results by Sudewa and Mudra (2018) reported that manure could increase the growth and yield of water spinach. Water spinach can be planted repeatedly, but subsequent plantings are not as good as the results of the first planting due to the decreased growth of water spinach.…”
Section: Introductionmentioning
confidence: 99%